The Effect of Education and Labor Force Participation on Local Taxes and Levies - Fran Reka Kurniawan; Sari Dewi (Universitas Multi Data Palembang, 2026)
The purpose of this study is to examine how labor force participation and educational attainment affect municipal tax and levy collections in Indonesia. Secondary panel data from 34 provinces between 2017 and 2024, sourced from the Directorate General of Fiscal Balance and the Central Bureau of Statistics, is used in the study. The analytical technique is panel data regression with robust standard errors. According to the estimation results, at the five percent significance level, there is no statistically significant relationship between labor force participation and education level and municipal tax and levy revenues. These results imply that social variables by themselves are no longer the primary drivers of rising municipal tax and levy revenues. Therefore, in order to increase local own-source revenue, local governments must take into account additional aspects including expanding the tax base, improving the quality of tax administration, and optimizing digital tax systems.